Desenvolvimento e validação de métodos bioanalíticos para quantificação da amoxicilina, norfloxacino e oxcarbazepina em estudos farmacocinéticos - Martins, Ismael Leite (2009)
A robust method for the determination of amoxicillin, norfloxacin, oxcarbazepine (OXC) and its active metabolite, 10,11-dihydro-10-hydroxycarbamazepine (MHD) in human plasma, using reversed-phase high-performance liquid chromatography (RP-HPLC) with ultraviolet, fluorescence and mass spectrometry detection, respectively, have been developed and valited. The methods involve precipitation of plasma protein with dichloromethane (amoxicillin), acetonitrile (amoxicillin and norfloxacin) and diethyl ether–diclhoromethane (60:40 v/v, oxcarbazepine), using cefadroxil, ciprofloxacin and deuterade carbamazepine (d10-carbamazepine) as internal standard (IS). Chromatographic separations were performed on a column Gemini C18 5 µm (150 X 4.6 mm), Synergi MAX-RP 4 µm (150 X 4.6 mm) and Luna C18 5 µm (150mm X 4.6 mm) with an elution system consisting of a mixture of 0.01 M buffer phosphate (pH 3.5)/acetonitrile (95:05 v/v), phosphate buffer–acetonitrile (85:15, v/v) and acetonitrile/water (50:50 v/v) + 20mM acetic acid, respectively. The calibration curve was linear, in the range of 0.5 to 40 µg/mL, 30 to 3500 ng/mL, 20 to 5250 ng/mL and 40 to 10,500 ng/mL. The recoveries at concentrations of 1.5, 15 and 30 µg/mL were foram 59.4%, 60.5% and 67.1% for amoxicillin; 90, 1400 and 2800 ng/mL were 103.5%, 100.2% and 100.2% for norfloxacin, 60, 2000 and 4000 ng/mL were 105.4, 89.2 and 92.8% for OXC and 120, 4000 and 8000 ng/mL were 88.4, 88.7 and 90.6% for MHD, respectively. The statistical evaluation of the developed method was conducted by examining within-batch and between-batch precision data, which were within the required limits. The methods were successfully applied in bioequivalence studies given 500 or 400-mg of the reference formulation / test amoxicillin and norfloxacin, and pharmacokinetic studies with formulation of oxcarbazepine suspension (6%) in healthy volunteers.